2002
DOI: 10.2134/jeq2002.1636
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides in Surface Water, Sediment, and Rainfall of the Northeastern Pantanal Basin, Brazil

Abstract: Within the last 25 years an intensive agriculture has developed in the highland regions of Mato Grosso state (Brazil), which involves frequent pesticide use in highly mechanized cash-crop cultures. To provide information on pesticide distribution and dynamics in the northeastern Pantanal basin (located in southern Mato Grosso), we monitored 29 pesticides and 3 metabolites in surface water, sediment, and rainwater of the study area during the main application season. In environmental samples, 19 pesticides and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
111
1
37

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(152 citation statements)
references
References 35 publications
3
111
1
37
Order By: Relevance
“…Total concentrations of metolachlor, trifluralin, nitrofen acetochlor, alachlor, and chlorpyriphos in water samples (in the range of 19.2-42.7 ng/1, with a mean value 29.7 ng/1) and in sediment samples (in the range of 0.568-2.93 ng/g, with a mean value 1.59 ng/g) are lower than that reported from the Northeastern Pantanal Basin, Brazil, by Laabs et al (2002), where total concentrations were found in the range of 31-56 ng/1, with a mean value 55 ng/l. Total concentrations were apparently higher in sediment samples because these pesticides are not found (below detection limits) in the Northeastern Pantanal Basin.…”
Section: Levels Of Pesticide Residues In Sediment and Water Samples Icontrasting
confidence: 55%
“…Total concentrations of metolachlor, trifluralin, nitrofen acetochlor, alachlor, and chlorpyriphos in water samples (in the range of 19.2-42.7 ng/1, with a mean value 29.7 ng/1) and in sediment samples (in the range of 0.568-2.93 ng/g, with a mean value 1.59 ng/g) are lower than that reported from the Northeastern Pantanal Basin, Brazil, by Laabs et al (2002), where total concentrations were found in the range of 31-56 ng/1, with a mean value 55 ng/l. Total concentrations were apparently higher in sediment samples because these pesticides are not found (below detection limits) in the Northeastern Pantanal Basin.…”
Section: Levels Of Pesticide Residues In Sediment and Water Samples Icontrasting
confidence: 55%
“…Consequently, the LOQ values for these compounds were between 0.050 and 0.206 μg L -1 as shown in Table 5. The detection limits obtained were in good agreement with those previously published by Panshin et al 17 and Pinto and Jardim, 18 but higher than the one obtained by Laabs et al 9 and Quintana et al 16 However, the last method used other sorbent material and GC-MS technique, Table 4. On the other hand, the LOD values were lower than or equal to the maximum admissible concentration established by the European Union for the sum of all pesticides (0.5 μg L -1 ) or for an individual compound in drinking water (0.1 μg L -1 ).…”
supporting
confidence: 90%
“…8 In another study, 29 pesticides and 3 metabolites were determined in surface water of northeastern area of Pantanal region and glifosate and its main metabolite were studied in water from a rice-growing area. [9][10] The present work reports the optimization of an SPE method for simultaneous determination of simazine, metribuzin, metolachlor, trifluralin, atrazine and two of its metabolites, deisopropylatrazine (DIA) and deethylatrazine (DEA), in water by means of gas chromatography using nitrogen-phosphorus detection. The pesticides selected are the most frequently used in this agricultural area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…após a aplicação que, provavelmente, foi causada por sua rápida volatilização em virtude das altas temperaturas da região. A presença de resíduos de agrotóxicos em amostras de água da chuva tem sido utilizada para demonstrar a volatilização desses compostos em países de clima temperado (Dubus et al, 2000;Vogel et al, 2008;Gish et al, 2011) e tropical (Laabs et al, 2002;Nogueira et al, 2012), inclusive com relatos da presença do endossulfam (Scheyer et al, 2005;Nogueira et al, 2012). Kennedy et al (2001) observaram volatilização de 70% do endossulfam após sua aplicação na cultura do algodoeiro, na Austrália.…”
Section: Methodsunclassified